(untitled) (Nexus International Journal of Science and Education, 2024)
This qualitative-phenomenological study explored the experiences of fifteen (15) high school students at Teofilo V. Fernandez National High School concerning using ChatGPT as an academic support in learning English. Employing Collaizi’s method of data analysis, the research utilized in-depth interviews and focus group discussions as data collection methods, with fifteen high school student participants chosen through purposive sampling, all with direct experience in using ChatGPT to learn English. The students’ experiences were divided into two—the good and bad experiences alike. The former encompasses students’ experiences in plagiarism, information accuracy and biases, and the potential of academic dishonesty. At the same time, the latter encapsulates the idea of ChatGPT as a tool to enhance English language learning. Despite these, students expressed that verifying processes from ChatGPT’s inputs, understanding topics before ChatGPT’s utilization, and using it as a supplementary tool helped them overcome the challenges. The study, however, emphasized the significance of the tool that personalizes students’ learning experiences and its benefits in helping non-native English speakers. Lastly, the students’ insight that ChatGPT and its AI counterparts need AI literacy for teachers and students to utilize these tools and platforms for their potential to improve learning outcomes. The study recommends that the Department of Education, classroom teachers, and students embrace such tools to adapt to 21st-century learning and innovations, paving the way for further AI tools to improve student outcomes.